The Phosphatidylinositol 3-Kinase (PI3K) Isoform Dependence of Tumor Formation Is Determined by the Genetic Mode of PI3K Pathway Activation Rather than by Tissue Type - Utermark, Tamara (American Society for Microbiology, 2014)
Previous work has shown that prostate cancer in a Pten-null murine model is dependent on the p110β isoform of phosphatidylinositol 3-kinase (PI3K), while breast cancer driven by either polyoma middle T antigen (MT) or HER2 is p110α dependent. Whether these differences in isoform dependence arise from tissue specificity or from the nature of the oncogenic signal activating the PI3K pathway is important, given increasing interest in using isoform-specific PI3K inhibitors in cancer therapy. To approach this question, we studied the PI3K isoform dependence of our recently constructed prostate cancer model driven by MT. Since MT activates a number of signaling pathways, we first confirmed that the MT-driven prostate cancer model was actually dependent on PI3K. A newly generated transgenic prostate line expressing an MT allele (Y315F) known to be defective for PI3K binding displayed a markedly reduced ability to drive tumor formation. We next selectively ablated expression of either p110α or p110β in mice in which wild-type MT was expressed in the prostate. We found that tumor formation driven by MT was significantly delayed by the loss of p110α expression, while ablation of p110β had no effect. Since the tumor formation driven by MT is p110α dependent in the prostate as well as in the mammary gland, our data suggest that PI3K isoform dependence is driven by the mode of PI3K pathway activation rather than by tissue type. IMPORTANCE Middle T antigen (MT), the oncogene of polyomavirus, can drive tumor formation in a variety of cell types and tissues. Interestingly, MT has no intrinsic enzymatic activity but instead functions by binding and activating cellular signaling proteins. One of the most important of these is the lipid kinase PI3K, which was first studied in MT immunoprecipitates. Ubiquitously expressed PI3K comes in two major isoforms: p110α and p110β. Previous work in animal models showed that p110α was the key isoform in breast tumors driven by oncogenes, including MT and HER2, while p110β was key in prostate tumors driven by Pten loss. We asked the simple question of whether a prostate tumor driven by MT depends on p110α, which would suggest that the mode of activation determines p110 isoform dependence, or p110β, which would suggest that tissue type determines isoform dependence. The clear answer is that MT depends on p110α in both the prostate and breast.